The Impact of Mergers and Acquisitions on Firm Performance: Evidence from the Pharmaceutical Industry - Kasetty, Soumya Ramesh (2009)
The recent past has witnessed a significant increase in mergers and acquisition activity. Firms mainly engage in mergers to achieve corporate growth and realise their business strategy. Mergers and Acquisitions has been a popular strategy among companies, but however they may not always improve firm performance. Various theoretical and empirical studies have been conducted to measure the impact of mergers and acquisitions. Theoretically mergers and acquisitions have shown to improve company performance due to diversification, synergy gains, economies of scale and various other factors. Empirically accounting based studies and stock market event based studies have all reached varied conclusions showing positive to negative to no impact on company performance.